Phase Transition Behaviour of Ising Spin Glass on the FCC Lattice - Thanh, Ngo Van; Tien, Hoang Dinh; Hung, Diep The (Communications in Physics, 2013)
In this work, we study the nature of phase transition in a face centered cubic (FCC) antiferromagnet with Ising spins. The spin-glass character depends on the concentration \(p\) of ferromagnetic bonds randomly generated into the system. We introduce a new quantity \(M_Q\) combined by the Edwards-Anderson order parameter \(Q\) and the standard magnetization \(M\). Note that, it is impossible to obtain the susceptibility defined by the variance of \(Q\) or \(M\), but we can do that for \(M_Q\). Using the standard Monte-Carlo and powerful Wang-Landau flat-histogram methods, we carry out in this work intensive simulations with many value of $p$. We show that the first-order transition has been destroyed with a tiny amount of ferromagnetic bond \(p\sim 0.01\). With increasing \(p\), the antiferromagnetic phase changes into a spin glass, and then to ferromagnetic phase.